Analysis of the implementation of the policy guidelines for sustainable bovine livestock farming 2022–2050 - Sandoval, Danny; Triana Ángel, Natalia; Burkart, Stefan (2024)
Cattle farming among the main agricultural activities in Colombia. However, the extensive nature of this activity generates strong social and environmental impacts such as land grabbing, expansion of agricultural frontier, increased greenhouse gas emissions, and deforestation. One of the main initiatives to promote the productive transformation towards more sustainability are the Policy Guidelines for Sustainable Bovine Livestock Farming 2022-2050 (Lineamientos de Política para la Ganadería Bovina Sostenible; LPGBS), which arose from a series of conversations among sector institutions and the national government. While the LPGBS are presented as the roadmap for cattle farming in Colombia, its implementation raises reservations among the participating institutions in the construction process and faces delays. This research analyses the status of the LPGBS to identify present difficulties and determine strategies to promote sustainability in cattle systems through capacity building. The methodology used is based on a mixed-methods approach. First, a literature review was conducted on studies related to the evaluation of public policies in the cattle sector. This information was complemented with 26 key informant interviews with experts from public and private institutions involved in the design of the LPGBS to obtain key perspectives and practical experiences to understand current difficulties and identify the necessary capacities to achieve the transition towards sustainable cattle farming. The results show that several difficulties arose during the LPGBS design stage: institutional weakness, low participation by government representatives, and little trust among actors were the main challenges during this stage. Regarding early achievements reached during these dialogues, the following were identified: Construction of the criteria for social, environmental, and productive sustainability, consolidation of the sustainability approach at the cattle landscape level, and regional participation. As necessary capacities to develop for promoting the implementation of the LPGBS, the following were identified: promotion of rural extension programs, access to financing programs, and implementation of a traceability system that allows monitoring and evaluation of these programs. These findings highlight the importance of generating policy evaluations in early stages, which allow identifying elements to correct on the fly, which becomes an important input for decision-makers and policy makers.